A peculiar new Pampatheriidae (Mammalia: Xenarthra: Cingulata) from the Pleistocene of Argentina and comments on Pampatheriidae diversity - Góis, F. (2015)
Pampatheriidae are a group of cingulates native to South American that are known from the middle Miocene to the lower Holocene. Two genera have been recognized between the lower Pleistocene and the lower Holocene: Pampatherium Gervais and Ameghino (Ensenadan, Bonaerian and Lujanian, lower Pleistocene-lower Holocene) and Holmesina Simpson (Blancan, Irvingtonian, upper Pliocene-lower Holocene). They have been mainly differentiated by their osteoderm morphology and cranio-dental characters. These taxa had a wide latitudinal distribution, extending from the southern part of South America (Península Valdés, Argentina) to North America (Florida, USA). In this contribution, we describe a new genus and species of Pampatheriidae for the lower and middle Pleistocene of Buenos Aires Province and for the upper Pleistocene of Santa Fe Province (Argentina).The new taxon is represented by disarticulated osteoderms, one skull element, two thoracic vertebrae and a right femur and patella. It has extremely complex osteoderm ornamentations and particular morphological characters of the cranial element and femur that are not found in any other species of the family. This new taxon, recorded in the lower-middle Pleistocene (Ensenadan Stage/Age) and in the upper Pleistocene-early Holocene (Lujanian Stage/Age), is incorporated to the Pleistocene mammal assemblage of South America. Finally, the Pampatheriidae diversity is greater during the Lujanian Stage/Age than the Ensenadan Stage/Age.